Smart and Solar Greenhouse Covers: Recent Developments and Future Perspectives - Maraveas, Chrysanthos; Loukatos, Dimitrios; Bartzanas, Thomas; Arvanitis, Konstantinos G.; Uijterwaal, Johannes Franciscus (Arjan) (Frontiers in Energy Research, 2021)
The examination of recent developments and future perspectives on smart and solar greenhouse covers is significant for commercial agriculture given that traditional greenhouse relied on external energy sources and fossil fuels to facilitate lighting, heating and forced cooling. The aim of this review article was to examine smart and solar materials covering greenhouse. However, the scope was limited to intelligent PhotoVoltaic (PV) systems, optimization of some material properties including smart covers, heat loading and the use of Internet of Things (IoT) to reduce the cost of operating greenhouse. As such, the following thematic areas were expounded in the research; intelligent PV systems, optimization of the Power Conversion Efficiency (PCE), Panel Generator Factor (PGF) and other material properties, heat loading future outlook and perspectives. The intelligent PV section focused on next-generation IoT and Artificial Neural Networks (ANN) systems for greenhouse automation while the optimization of material parameters emphasized quantum dots, semi-transparent organic solar cells, Pb-based and Pb-based PVs and three dimensional (3D) printing. The evaluation translated to better understanding of the future outlook of the energy-independent greenhouse. Greenhouse fitted with transparent PV roofs are a sustainable alternative given that the energy generated was 100% renewable and economical. Conservative estimates further indicated that the replacement of conventional sources of energy with solar would translate to 40–60% energy cost savings. The economic savings were demonstrated by the Levelized cost of energy. A key constraint regarded the limited commercialization of emerging innovations, including transparent and semitransparent PV modules made of Pb-quantum dots, and amorphous tungsten oxide (WO3) films, with desirable electrochromic properties such as reversible color changes. In addition to intelligent energy harvesting, smart IoT-based materials embedded with thermal, humidity, and water sensors improved thermal regulation, frost mitigation and prevention, and the management of pests and disease. In turn, this translated to lower post-harvest losses and better yields and revenues.